OŞ ILAHIYAT FAKÜLTESI ÖGRENCILERI ILE ILGILI BAZI TESPITLER VE TEKLIFLER - DAM, Hasan (Scientific Journal of Faculty of Theology, 2011)
The aim of this sfudy is to determine the profiles of the students at the Osh State University Theology Faculty in Kyrgyzstan; to expose their thoughts expectations and problems on educational process and to develop appropriate solutions, thus to contribute to the achievement of the objectives of the faculty. For this purpose, 80 students were chosen attended at Osh Theology Faculty as a in the academic year of.2010-2011. The research data largely based on the survey (inquiry) applications. The data relevant to the frequency and comparative distribution of the findings taken from the field investigation were evaluated.